A reassessment of the taxonomic status of Paraglyptodon Castellanos, 1932 (Mammalia, Cingulata, Glyptodontia) - Cruz, Laura E. (2016)
Castellanos described and published about new genera of glyptodonts, according to a phylogenetic scheme mainly based on the evolution of the external surface of the dorsal carapace. Among these new genera, Castellanos proposed Paraglyptodon as the predecessor of Glyptodon, and included within Paraglyptodon all known species of Glyptodontinae recovered from “horizontes pre-Ensenadenses”, and within Glyptodon all known species from “Horizontes pampeanos”, restricting the latter to the Quaternary. All the species that belong to Paraglyptodon, that is Paraglyptodon chapalmalensis, Paraglyptodon uquiensis, Paraglyptodon dubius, and Paraglyptodon paranensis were established based on one, two or few osteoderms, mostly from the dorsal carapace. Regarding P. paranensis and P. dubius, Oliva and collaborators consider the first as a nomen vanum, representing an indeterminate Glyptodontinae, and the second as a synonym of P. chapalmalensis. Upon re-examination of the holotypes of P. chapalmalensis and P. uquiensis together with their comparison with other well-known specimens of glyptodonts, mainly with Glyptodon (of both juvenile and adult stages), we found the same ornamentation in different sections of the dorsal carapaces, particularly in P. chapalmalensis and in juvenile stages of Glyptodon spp.We could not identify features that would allow us to make a distinction between the holotype of P. uquiensis and Glyptodon spp. Therefore, we consider that a new taxon guide for naming the Upper Chapadmalalan biozone is necessary. The biostratigraphic range of Glyptodon could possibly be extended to the late Pliocene. However, new records and studies are needed to verify the existence of this taxon in the Chapadmalalan Stage/Age in its type locality.